Hybrid forms of the Culex pipiens Complex (Diptera: Culicidae): New records in La Pampa Province, Argentina - Diez, Fernando (2012)
The present investigation revealed the existence of hybrids belonging to the Culex pipiens Complex in four localities of La Pampa Province, Argentina, thus expanding the distribution of the hybrid form south to the northeast of that province. The identification was based on characters of the male genitalia and the siphonal index of the fourth-instar larval exuviae. A summary of the geographical distribution of species of Culex pipiens complex in Argentina is also presented here.